2008
DOI: 10.1068/a38419
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Climate Change through Green Buildings and Smart Growth

Abstract: IntroductionGreen buildings and smart growth strategies are key to reducing global greenhouse gas (GHG) emissions in the future. In the United States, as in most developed countries, the energy requirements of buildings account for more than one third of GHG emissions. Approximately 43% of US carbon dioxide (CO 2 ) emissions result from the energy services required by residential, commercial, and industrial buildings, while transportation accounts for 32% and industry accounts for 25% (Brown et al, 2005). Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 16 publications
0
57
0
1
Order By: Relevance
“…Globally, urban areas are estimated to account for more than 80 % of total greenhouse gas (GHG) emissions [3,4]. Energy expenditures in the US constitute a significant and rising share of regular household spending, with a disproportionate impact on lower income households [5,6]. Consumption in other parts of the world, though lower, shows similar upward trajectories [7].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Globally, urban areas are estimated to account for more than 80 % of total greenhouse gas (GHG) emissions [3,4]. Energy expenditures in the US constitute a significant and rising share of regular household spending, with a disproportionate impact on lower income households [5,6]. Consumption in other parts of the world, though lower, shows similar upward trajectories [7].…”
Section: Introductionmentioning
confidence: 94%
“…Pitt [37•], in a recent study of climate action planning, found that a compact housing scenario for future urban growth could decrease residential energy us by as much as 36 %. According to Brown and Southworth [5], approximately 63 % of houses in the USA are single-family detached units, accounting for 73 % of residential energy consumption. Schipper et al [38] estimate that housing characteristics account for approximately 50 % of a home's energy use, while household characteristics and their lifestyle activities account for the remaining amount.…”
Section: The Energy Use and Urban Form Connectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…If there are inefficient buildings, such will have tremendous impact on the environment during their lifespan (Darko et al, 2013). Carbon-emissions mitigations in building is beneficial, especially for the low-income household (Brown & Southworth, 2006) because it "increased access to energy services, improved indoor and outdoor air quality, as well as increased comfort, health and quality of life, job creation and economic competitiveness" (Li & Colombier, 2009). And, as such, proponents of energy-efficient buildings have argued that it is one of the least-costly approaches to mitigating greenhouse gas emissions by designing and constructing a climate-friendly built environment and how buildings are linked with other socio-economic amenities and infrastructures (Reddy, 2010).…”
Section: Reducing the Impacts Of Climate Change Through Energy Efficimentioning
confidence: 99%